TINJAUAN HUKUM ISLAM TERHADAP PRAKTIK “DEREP PARI” DI DESA TINOMBALA BARAT - Yaumil Qodriyah; Sapruddin Sapruddin; Abidin Abidin (Program Studi Hukum Ekonomi Syariah, Fakultas Syariah, Universitas Islam Negeri (UIN) Datokarama Palu, 2021)
Abstract The discussion of this research is focused on the description of Islamic law related to the practice of Derep Pari in West Tinombala Village, Ongka Malino District, Parigi Mutong Regency, so that the formulation of questions that must be answered are (1) What is the description of the practice of Derep Pari in West Tinombala? (2) What is the law of derep pari in the village of West Tinombala in Islamic teachings?. The results showed that (1) In the practice of Derep-Pari in Tinombala Barat Village, the wage system was determined based on the results of the agreement. (2) From the perspective of Islamic law, the wage system in Tinombala Barat Village is in accordance with Islamic law, where the operational principles and provisions already include aspects of justice because the wages paid to workers are given immediately after the work is completed and in the provision of wages in accordance with the agreement or in accordance with by agreement.